The Taxonomy of Selected Economic Timber Species in Benue State, Nigeria: A Phylogenetic Approach to Sustainable Forest Utilization for the Prediction of Species Traits and Responses - Okpara, Onyinyechi; Ngbede, William (Journal of Sustainable Natural Resources, 2026)
Illegal falling of economic trees in Benue State has led to destruction of ecosystems and habitats of rare species and possible extinction of many trees. The aim of this study was to investigate the taxonomy of economic trees in Benue State and trace phylogenetic relationships for conservation purposes. Random selection of four tree species located at Joseph Sarwuan Tarka University, Makurdi (JOSTUM) were investigated: Bombax ceiba, Adansonia digitata, Ceiba pentandra, and Syzygium cumin. Morphological variation and genetic diversity of each sample were evaluated using Random Amplified Polymorphic DNA (RAPD) markers. Phylogenetic trees to elucidate evolutionary relationships among these species were constructed. Morphological assessments focused on key traits such as leaf shape, flower structure, and fruit characteristics, revealing distinct variations that correlate with species identification. Molecular analysis using RAPD markers yielded informative genetic profiles, demonstrating significant polymorphism across the studied taxa. The constructed phylogenetic tree illustrates the genetic relationships, highlighting evolutionary patterns and divergence among the studied species. Overall, this study provides valuable insights into the morphological and genetic diversity of these economically and ecologically important plants, contributing to their conservation and utilization strategies.